Post-operative intravenous fluid administration for infant cleft surgery: An observational study. Issue 4 (April 2021) - Rangaraju, Madhumitha; Slator, Rona; Richard, Bruce
Summary: Objective: To investigate post-operative intravenous fluid administration and length of stay in a single site cleft centre. Previous publications have linked increased length of stay following primary cleft surgery to the administration of intravenous fluids post-operatively. Materials and Methods: One hundred and ten primary cleft operations were conducted from May 2015 to April 2016 on non-syndromic infants. At West Midlands Cleft Centre, there are three cleft surgeons and 20 paediatric anaesthetists. This observational study compares classification of cleft type and surgical procedure with intravenous fluid administration, time taken to tolerate oral feeding, and length of stay. Results: Cleft lip repair infants had the shortest length of stay in hospital, 25 h 8 min (median) and 33% had intravenous fluids. The palate repair only and lip and palate repair children had a median length of stay of 29 h 20 min and 29 h 0 min respectively, A total of 79% and 76% of these groups had intravenous fluids administered. Cleft lip repair infants fed in significantly less time than palate alone or lip and palate operations (p values 0.00 and 0.03, respectively). Conclusion: Cleft lip repair only infants feed well post-operatively and rarely require intravenous fluids. Infants having cleft repair involving the palate are slower to feed orally, and may require fluids due to poor oral intake. Intravenous fluids following lip repair is associated with longer hospital stay. We suggest intravenous fluids may not be needed routinely following cleft lip repair, but should always be considered following repair involving the palate.